KARAKTERISASI EKSTRAK KASAR FITASE TERMOFILIK DARI BAKTERI KAWAH IJEN BANYUWANGI, ISOLAT AP-17 - Aline Puspita Kusumadjaja; Tutuk Budiati; Sajidan; Ni Nyoman Tri Puspaningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Crude thermophilic phytase was produced by isolate AP-17 that has been isolated from Ijen Crater Banyuwangi. Based on Gram test, isolate AP-17 was gram positive spore forming rod shape bacteria so that it was identified as Bacillus sp. AP-17. Crude thermophilic phytase isolated from Bacillus sp. AP-17 had the optimum temperature at 75° C with activity of 0.1413 U/ml, and its optimum pH was at pH 6 with activity of 0.0875 U/ml. The enzyme was stable when heated at 75° C for three hours and still had 90% activity when it was exposed at pH 5–8, optimum temperature, for one hour.